Mouse and human CD8+ CD28low regulatory T lymphocytes differentiate in the thymus. Issue 2 (23rd March 2016) - Vuddamalay, Yirajen; Attia, Mehdi; Vicente, Rita; Pomié, Céline; Enault, Geneviève; Leobon, Bertrand; Joffre, Olivier; Romagnoli, Paola; van Meerwijk, Joost P.M.
Summary: Regulatory T (Treg) lymphocytes play a central role in the control of immune responses and so maintain immune tolerance and homeostasis. In mice, expression of the CD8 co‐receptor and low levels of the co‐stimulatory molecule CD28 characterizes a Treg cell population that exerts potent suppressive function in vitro and efficiently controls experimental immunopathology in vivo . It has remained unclear if CD8 + CD28 low Treg cells develop in the thymus or represent a population of chronically activated conventional T cells differentiating into Treg cells in the periphery, as suggested by their CD28 low phenotype. We demonstrate that functional CD8 + CD28 low Treg cells are present in the thymus and that these cells develop locally and are not recirculating from the periphery. Differentiation of CD8 + CD28 low Treg cells requires MHC class I expression on radioresistant but not on haematopoietic thymic stromal cells. In contrast to other Treg cells, CD8 + CD28 low Treg cells develop simultaneously with CD8 + CD28 high conventional T cells. We also identified a novel homologous naive CD8 + CD28 low T‐cell population with immunosuppressive properties in human blood and thymus. Combined, our data demonstrate that CD8 + CD28 low cells can develop in the thymus of mice and suggest that the same is true in humans.